Analysis of Customer Satisfaction towards Waste Transportation Using the Important Performance Analysis Method - Muhdar Muhdar; Harvian Bagus Dewantara; Eko Afrianto (Trescode Green Organization, 2024)
This research aims to identify quality aspects that cause customer satisfaction in waste transportation at the Banyuwangi Regency Environmental Service. The data used in this research is primary data. The data processing method in this research uses validity tests and reliability tests which are data instrument test analysis methods, as well as testing physical evidence (tangible value) which is an attribute of the five dimensions of service quality, dependability (reliability), responsiveness, sense of security and empathy. The research results show that the gap value in the reliability aspect is very low, this shows that the service quality of the Banyuwangi Regency Environmental Service is very satisfying to customers. Meanwhile, the responsiveness dimension has the biggest gap, this shows that customers are dissatisfied with the responsiveness of the Banyuwangi Regency Environmental Service in overcoming existing problems. This will of course be a reference for improving the quality of services of the Banyuwangi Regency Environmental Service.